2016
DOI: 10.1186/s13023-016-0410-6
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of specialized adult care for phenylketonuria – a single-centre experience

Abstract: BackgroundSpecialized adult care of phenylketonuria (PKU) patients is of increasing importance. Adult outpatient clinics for inherited errors of metabolism can help to achieve this task, but experience is limited. Ten years after establishment of a coordinated transition process and specialised adult care for inherited metabolic diseases, adult PKU care was evaluated with respect to metabolic control, therapy satisfaction, life satisfaction, sociodemographic data, economical welfare as well as pregnancy outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 30 publications
5
32
0
1
Order By: Relevance
“…However, the impact of dietary management on QoL was comparable between patients with classical and mild PKU, possibly reflecting dietary relaxation during adulthood . In another study, patients on a restricted diet reported higher scores of general life‐satisfaction than both an off‐diet patient group and a reference sample . Moreover, some data suggest that returning to a strict diet after discontinuation for at least 3 months can significantly improve the subjective well‐being of patients, according to evaluation with the Psychological General Well‐Being Index …”
Section: Quality Of Lifementioning
confidence: 99%
See 2 more Smart Citations
“…However, the impact of dietary management on QoL was comparable between patients with classical and mild PKU, possibly reflecting dietary relaxation during adulthood . In another study, patients on a restricted diet reported higher scores of general life‐satisfaction than both an off‐diet patient group and a reference sample . Moreover, some data suggest that returning to a strict diet after discontinuation for at least 3 months can significantly improve the subjective well‐being of patients, according to evaluation with the Psychological General Well‐Being Index …”
Section: Quality Of Lifementioning
confidence: 99%
“…In the first study, patients with PKU, 96% of whom were on a restricted diet, achieved lower levels of academic achievement, specifically for graduation at senior high school level, compared with the general population . The second study found that educational attainment was only lower in patients with PKU whose treatment was interrupted (for at least 4 years starting at the age of 7‐14 years), while patients who had been continuously treated until the end of adolescence demonstrated comparable education status to the census population . Nevertheless, income was comparable between patients with PKU and the census population, regardless of therapy interruption …”
Section: Social Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Presymptomatically diagnosed and treated individuals often remain asymptomatic until adolescence/adulthood. In many countries, however, there is still a need to establish a transition from pediatric to adult health care and long-term care to prevent a drop-out of medical care and to support lifelong compliance analogous to other inborn metabolic diseases (Mutze et al 2011;Mutze et al 2016). Although metabolic crisis occur rarely in adulthood, prolonged fasting and catabolic stress should be avoided life-long to prevent metabolic decompensations (Feinstein and O'Brien 2003)byor al or intravenous carbohydrate supply (4-6 g/kg BW/d) and if necessary additional carnitine supplementation (50-100 mg/ kg BW/d).…”
Section: Managementmentioning
confidence: 99%
“…However, evidences suggest that high plasma Phe concentrations can cause neurological and psychological disorders in adulthood (Waisbren et al 2007;ten Hoedt et al 2011;Sharman et al 2012;Bilder et al 2013;Okano and Nagasaka 2013;Weglage et al 2013). Thus, maintaining a Phe-restricted diet in adult PKU patients is still debated (Demirkol et al 2011;ten Hoedt et al 2011;Trefz et al 2011;Hanley 2013;Mutze et al 2016). Several hypotheses about the pathophysiology of brain injury in PKU have been discussed but the mechanisms remain unclear and seem to be multifactorial (Bone et al 2012).…”
Section: Introductionmentioning
confidence: 99%